2015
DOI: 10.1039/c5cp05045f
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous transition of a water droplet from the Wenzel state to the Cassie state: a molecular dynamics simulation study

Abstract: It is widely accepted that the superhydrophobic state is attributed to the formation of the Cassie state. The Cassie state is mostly metastable, which can be turned into the Wenzel state. Therefore, the superhydrophobic state is generally considered to be unstable. In this study, the wetting behaviors of a water droplet on different pillar surfaces are simulated. The spontaneous transition from the Wenzel state to the Cassie state is achieved, which is significant for the stable existence of superhydrophobicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…It has been shown that decreasing 3 SL can effectively enhance surface hydrophobicity and this method has been widely used in previous studies. 34,35 All of our MD simulations were carried out on Gromacs 5.1.2. 36 Provided that the realistic density of liquid water is 996.5 kg m À3 at 300 K, there were 15 300 water molecules included in the modeling domain.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that decreasing 3 SL can effectively enhance surface hydrophobicity and this method has been widely used in previous studies. 34,35 All of our MD simulations were carried out on Gromacs 5.1.2. 36 Provided that the realistic density of liquid water is 996.5 kg m À3 at 300 K, there were 15 300 water molecules included in the modeling domain.…”
Section: Methodsmentioning
confidence: 99%
“…The hierarchical textures can be manufactured with photolithography and deep reactive-ion etching technology 39 . [42][43][44][45] . And the results of MDS is in consistence with the experiments in many aspects [42][43][44] .…”
Section: Effects Of Micro-nano Hierarchical Textures On C-w Transitiomentioning
confidence: 98%
“…In this context, it is worth exhibiting monostable Cassie states where even an accidental transition to the undesired Wenzel state, due to force fluctuations such as encountered in an impact (37) or to pressure applied on the liquid (16,17,33,(46)(47)(48)(49)(50), can be repaired owing to the absence of barrier between both states. Because reported Wenzel-to-Cassie (W2C) transitions generally involve either an external energy input (17,49,(51)(52)(53) or a potential energy release (35,(54)(55)(56), monostable Cassie states might be seen as unreal (57), but we describe here such situations and criteria for achieving them. Our hope is that these findings will shed new light on our fundamental understanding of water repellency.…”
mentioning
confidence: 99%